Environmentally friendly bleaching of cotton using laccases - Pereira, Luciana (2005)
A new strain of Trametes hirsuta was found to oxidize various cotton flavonoids. Here we show that laccases of this organism were responsible for oxidation of the flavonoids morin, luteolin, rutin and quercetin. Out of two laccases produced by T. hirsuta (60.7 and 51.0 kDa) the more prominent 60.7 kDa laccase was purified and showed Km and kcat values of 75.5, 20.9 and 49.4 μM and 72.5, 96.3 and 32.7 s−1, hours on ABTS, syringaldazide and DMP, respectively. Pretreatment of cotton with the T. hirsuta laccase resulted in a whiteness increase of 8.5%.